The Spatial and Emission Properties of the Large [O iii] Emission Nebula Near M31 - Robert A. Fesen; Stefan Kimeswenger; J. Michael Shull; Marcel Drechsler; Xavier Strottner; Yann Sainty; Bray Falls; Christophe Vergnes; Nicolas Martino; Sean Walker; Justin Rupert (The Astrophysical Journal, 2023)
Drechsler et al. reported the unexpected discovery of a 1.°5 long [O iii ] emission nebula 1.°2 southeast of the M31 nucleus. Here we present additional images of this large emission arc, called the Strottner–Drechsler–Sainty Object (SDSO), along with radial velocity and flux measurements from low-dispersion spectra. Independent sets of [O iii ] images show SDSO to be composed of broad streaks of diffuse emission aligned northeast–southwest. Deep H α images reveal no strong coincident emission suggesting a high [O iii ]/H α ratio. We also find no other [O iii ] emission nebulosity as bright as SDSO within several degrees of M31 and no filamentary H α emission connected to SDSO. Optical spectra taken along the nebula’s northern limb reveal [O iii ] λ λ 4959, 5007 emissions matching the location and extent seen in our [O iii ] images. The heliocentric velocity of this [O iii ] nebulosity is −9.8 ± 6.8 km s ^−1 with a peak surface brightness of (4 ± 2) × 10 ^−18 erg s ^−1 cm ^−2 arcsec ^−2 (∼0.55 Rayleigh). We discuss SDSO as a possible unrecognized supernova remnant, a large and unusually nearby planetary nebula, a stellar bow shock nebula, or an interaction of M31's outer halo with Local Group circumgalactic gas. We conclude that galactic origins for SDSO are unlikely and favor instead an extragalactic M31 halo–circumgalactic cloud interaction scenario, despite the nebula’s low radial velocity. We then describe new observations that may help resolve the nature and origin of this large nebulosity so close to M31 in the sky.